2010
DOI: 10.5213/inj.2010.14.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of "Tension-free" Placement of Gynemesh PS for the Treatment of Anterior Vaginal Wall Prolapse

Abstract: Purpose: To evaluate the efficacy and safety of the tension-free placement of a monofilament polypropylene mesh for the repair of an anterior vaginal wall prolapse (AVWP). Materials and Methods: Women aged ≥ 30 years with an AVWP stage of II or greater were included. Forty-nine women underwent trans-vaginal repair using a Gynemesh TM PS. Forty-six women who had symptomatic stress urinary incontinence received a midurethral sling (MUS). At the 12-month follow-up, evaluations were made for changes in the Pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Pikaart et al also indicated that polypropylene mesh degradation required removing the sling portion that eroded into the bladder [13]. Whereas, Lee et al convinced that trans-vaginal repair of an anterior vaginal wall prolapse with the monofilament polypropylene mesh is an effective and safe procedure [14]. Achtariet al [15] compared the erosion rates of two prostheses: a polypropylene nonabsorbable, monofilament, macroporous mesh and a composite polypropylene/polyglactin 910, mono/multifilament, absorbable/nonabsorbable mesh.…”
Section: Introductionmentioning
confidence: 99%
“…Pikaart et al also indicated that polypropylene mesh degradation required removing the sling portion that eroded into the bladder [13]. Whereas, Lee et al convinced that trans-vaginal repair of an anterior vaginal wall prolapse with the monofilament polypropylene mesh is an effective and safe procedure [14]. Achtariet al [15] compared the erosion rates of two prostheses: a polypropylene nonabsorbable, monofilament, macroporous mesh and a composite polypropylene/polyglactin 910, mono/multifilament, absorbable/nonabsorbable mesh.…”
Section: Introductionmentioning
confidence: 99%
“…Paraiso was the only one to report a pelvic abscess after surgery [5]. In 11 non-randomized studies (623 patients), nine of which using NAS meshes, no post-surgical infection was detected [33,[36][37][38][39][40][41][42][43][44][45]. Six studies with NAS meshes reported post-surgical hyperthermia, meaning 3.15% out of 755 cases [46][47][48][49][50][51].…”
Section: Infectionmentioning
confidence: 99%
“…Seul Paraiso rapporte la survenue d'un abcès pelvien dans les suites opératoires [6]. Dans 11 études non randomisées (soit 623) patientes), dont neuf portant sur des prothèses NRS, aucune complication infectieuse n'a été notée en période postopératoire [28,[31][32][33][34][35][36][37][38][39][40]. Six études portant sur des prothèses NRS rapportent une hyperthermie dans 3,15 % des cas en moyenne sur 755 patientes traitées [41][42][43][44][45][46].…”
Section: Infectionunclassified